The Implementation of Problem-Based Learning Approach to Improve Students' Motivation and Learning Outcomes in Information and Communication Technology Subject - Lidya Lestari Hutagaol (PT. Mifandi Mandiri Digital, 2024)
This classroom action research aimed to improve students’ learning motivation and academic achievement through the implementation of the Problem-Based Learning (PBL) model in Grade VII at SMP Advent Medan. Employing a descriptive qualitative approach, the research was conducted over two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were all students in the selected class. The research variables included the PBL model, students’ learning motivation, and learning outcomes. Data were collected using observation sheets, questionnaires, and achievement tests. The findings revealed that the application of the PBL model significantly enhanced students’ motivation to learn and improved their learning outcomes in the Information and Communication Technology subject.